Cultivation of auricularia polytricha mont. sacc (Black Jelly Mushroom) using oil palm wastes / Dang Lelamurni Abd. Razak - Abd. Razak, Dang Lelamurni (2013)
The increasing demand for continuous and quality supply of many types of mushrooms has drawn much attention and research to find potential substrate and domesticating the cultivation several species of edible mushrooms to suit local environmental conditions and resources. One of the popular mushrooms among Malaysians due to its nutritional and medicinal values, Auricularia polytricha or Black Jelly, offers high income to local growers due to its ability to grow and fruit in tropical region such as Malaysia. The availability of a wide variety of agro-industrial byproducts rich in lignocellulose and other materials required for mushroom growth should be explored and used as the substrate ingredients for the cultivation of A. polytricha as well as other mushroom species. This present study consisted of two main parts, namely the study of A. polytricha spawn production and formulation of fruiting substrates using oil palm wastes. The best substrate for production of spawn / inoculum was determined by comparing A. polytricha mycelia growth on several types of grains. It was found that crushed corn soaked for 4 hours, without adjusting its moisture content and pH and with no addition of supplement or adjustment of C:N ratio was the optimum substrate to support mycelia growth of A. polytricha at 6±1 mm/day growth rate. Corn (uncrushed) supported the lowest mycelia growth rate, while soybean and peeled soybean were deemed as unsuitable because of their high contamination rate. For fruiting substrate, the potential of using agricultural and industrial wastes was evaluated using several formulations of selected oil palm wastes combined with sawdust and also supplemented with selected nitrogen sources. The best substrate formulations selected were sawdust (SD) + oil palm frond (OPF) at a ratio of 90:10 supplemented with 15% spent grain (SG) and sawdust (SD) + empty fruit bunch (EFB) at a ratio of 50:50 supplemented with 10% spent grain (SG) with mycelia growth rates of 8±1 mm/day and iii 7±1 mm/day respectively. These two formulations were then subjected to different moisture content levels (65%, 75% and 85%). Highest total fresh mushroom yield of 43.3% was obtained on SD+OPF (90:10) + 15% SG at 85% moisture content, followed closely by SD+EFB (50:50) + 10% SG with 40.4% total yield, also at 85% moisture content. Each of the substrate formulations at 85% moisture content gave the highest biological efficiencies (BE) at 288.9% and 260.7% respectively. Both yield and biological efficiency of A. polytricha on these two formulations were almost three times higher when compared to sawdust substrate alone, thus proving the potential of these formulations to improve yield of this mushroom. Analysis of nutrient content of A. polytricha sporophores grown on SD+OPF (90:10) + 15% SG proved that this mushroom contains eight essential amino acids at levels ranging from 0.007 to 0.05%. In addition, cultivated A. polytricha in this study was found to be a valuable source of protein, carbohydrates, crude fibre, magnesium, potassium, manganese and phosphorus with values greater than 15% of the percentage daily portion based on RDA for each nutrient.